PENGARUH WORD OF MOUTH DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KEPUTUSAN ANGGOTA BERPARTISIPASI AKTIF DENGAN MANAGEMENT TRUST SEBAGAI VARIABEL MODERASI PADA KOPERASI CIPTA SEJAHTERA PANGKALPINANG - Ririn Dian Lentari (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
Cooperatives grow and develop from, by and for members, so that the decision of members to actively participate is very important for the development and survival of the Cooperative. Currently the active participation rate of members of the Pangkalpinang Cipta Sejahtera Cooperative in terms of saving, borrowing and installments is very low, this is allegedly due to the covid-19 pandemic. This research aims to examine whether word of mouth, customer relationship management and trust management have a significant effect on members' decisions to actively participate, and whether trust management moderates word of mouth and customer relationship management on members' decisions to actively participate. This research is a quantitative research, the number of samples is 129 with sampling using purposive sampling technique. The data analysis technique uses path analysis with PLS-SEM, utilizing the SMART-PLS version 3.0 program. The results of the research stated: Word of Mouth has a significant positive effect on members' decisions to actively participate. Customer Relationshikp Management has a significant positive effect on members' decisions to actively participate. Management trust has a significant positive effect on members' decisions to actively participate. The moderating nature of trust management is to weaken the influence of word of mouth on members' decisions to actively participate and strengthen the influence of customer relationship management on members' decisions to actively participate.Word of Mouth